The Intake of Dietary Lipids Improves Glucose Tolerance via Modulating Gut Microbiota - HANEISHI, Yuri; WATANABE, Saya; OKADA, Ayana; TAKEMAE, Hitoshi; BASTONI, Deborah; TREPPICCIONE, Lucia; SAGGESE, Anella; MIZUTANI, Tetsuya; ROSSI, Mauro; MIYAMOTO, Junki (Journal of Nutritional Science and Vitaminology, 2024)
The composition of gut microbiota is determined not only by genetic factors but also by environmental factors, such as diet, exercise, and disease conditions. Among these factors, diet is crucial in changing the gut microbial composition. Dietary lipids composed of different fatty acids not only alter host metabolism but also have a significant impact on the composition of gut microbiota. However, the molecular mechanisms underlying the relationship between these host effects and their impact on gut microbiota remain unclear. Here, we demonstrated that intake of different dietary lipids improved glucose tolerance by modulating gut microbiota. The results of our analysis show that the taxa of bacteria that increase in number as a result of dietary lipid intake play an important role in glucose metabolism. Thus, we have identified a new mechanism underlying the function of dietary lipids in regulating glucose homeostasis. Our findings contribute to possible new methods to prevent and treat metabolic disorders by modifying the composition of gut microbiota.